2006
DOI: 10.2134/jeq2005.0059
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Linking the Effects of Parathion in Soil to its Degradation and Bioavailability Kinetics

Abstract: Parathion is an insecticide of a group of highly toxic organophosphorus compounds. To investigate the dissipation and toxicological impact of parathion [O,O-diethyl O-(4-nitrophenyl) phosphorothioate] and its highly toxic metabolite, paraoxon, soil laboratory experiments were conducted in columns during a 19-d experiment under variably saturated conditions. Water and pesticide transport, sorption, and biodegradation of parathion were measured in three soil pools (soluble phase, weakly and strongly sorbed phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…Sparks has emphasized the importance of the kinetics and mechanisms. 7 Consistent with these other reports, [6][7][8][9][10][11][12][13][14][15][16][17][18] the experimental curves in Fig. 1 show that sorption, desorption, and chemical reaction were all strongly dynamic.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Sparks has emphasized the importance of the kinetics and mechanisms. 7 Consistent with these other reports, [6][7][8][9][10][11][12][13][14][15][16][17][18] the experimental curves in Fig. 1 show that sorption, desorption, and chemical reaction were all strongly dynamic.…”
Section: Introductionsupporting
confidence: 85%
“…7 Several authors have reported the dynamic nature of pesticide behaviour in soils. [8][9][10][11][12][13][14][15][16][17][18] They all reported that the pesticide interactions with soils changed with time during their experiments, so that equilibrium calculations would not have been valid. Because independent studies with different combinations of pesticides and soils were used, the phenomenon is evidently quite general.…”
Section: Introductionmentioning
confidence: 99%
“…For example, variability of herbicide dissipation for the pesticide isoproturon has been related to sorption to clay (Alletto et al, 2006) and extractability (Charnay et al, 2005), and several studies have demonstrated interactive effects between organic matter content, microbial degradation, and sorption processes (Bollag et al, 1992; Di et al, 1998; Madsen et al, 2000). Also, several publications provide a descriptive approach to the effect on pesticide degradation, i.e., bioavailability (Shelton and Doherty, 1997; Reid et al, 2000; Guo et al, 2000; Delle Site, 2001; Saffih‐Hdadi et al, 2006). In contrast, it has recently been suggested that the decrease in pesticide biodegradation with soil depth may be caused by an increase in the lag phase of the microbial degradation process rather than a decrease in bioavailability (Bending and Rodriguez‐Cruz, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As pesticides and metabolites are increasingly detected in groundwater (4), it is imperative to evaluate the ability of these environmental fate models to predict the long-term leaching of pesticides and especially of their metabolites. However, such studies have not hitherto been reported in the literature (5).…”
Section: Introductionmentioning
confidence: 93%